2016
DOI: 10.1007/s11748-016-0643-2
|View full text |Cite|
|
Sign up to set email alerts
|

Minimally invasive anterior chest wall lifting technique for thoracoscopic mediastinal approach

Abstract: Anterior chest wall lifting facilitates a wide view and allows easy access during thoracoscopic surgery in a supine position for anterior mediastinal lesions. We previously reported an anterior chest wall lifting method for a thymectomy that utilizes our original costal hooks. Here, we present a less invasive method that can be performed with only a needle puncture, i.e., a metal plate placed under the ribs is lifted with a wire inserted through the anterior chest wall. We have applied this novel 'T-lifting me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[24][25][26] A limited number of studies have explored the topic of chest wall resections, with one particularly emphasizing the benefits of utilizing immersive technologies. 27,28 A study with medical students showed that MR could be used effectively and with a high acceptance in addition to traditional technology to simulate preoperative planning in lung cancer surgery. 29 Very few studies published the use of a VR simulation system for preoperative planning for VATS segmentectomy with promising results in terms of usability and evaluation of anatomic structures.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] A limited number of studies have explored the topic of chest wall resections, with one particularly emphasizing the benefits of utilizing immersive technologies. 27,28 A study with medical students showed that MR could be used effectively and with a high acceptance in addition to traditional technology to simulate preoperative planning in lung cancer surgery. 29 Very few studies published the use of a VR simulation system for preoperative planning for VATS segmentectomy with promising results in terms of usability and evaluation of anatomic structures.…”
Section: Discussionmentioning
confidence: 99%
“…At Osaka University, surgeons including this author in 2002 developed a method for pulling upward the frontal rib bone with a metal rib hook, and reported its use and outcomes as part of an extended thymectomy ( 22 ) ( Figure 6 ). Later, a puncture-type lifting system (T-lifting system, Sonne Medical Co., Tokyo, Japan) was designed, and both minimal invasiveness and operability were found to be enhanced while effectiveness was maintained ( 23 ) ( Figure 7 ).…”
Section: Chest Wall Lifting Methods For Endoscopic Surgerymentioning
confidence: 99%
“…Anterior chest wall lifting method ( 54 ): this method is predominantly employed within a unilateral video-assisted thoracoscopic surgery (VATS) approach. The procedure entails raising the anterior chest wall to facilitate access to the thymus, presenting an alternative avenue to sternotomy.…”
Section: Surgical Approachmentioning
confidence: 99%